Familial Creutzfeldt-Jakob disease with temporal and spatial separation of affected members - Mitrova, E; Lowenthal, A; Appeal, B (European journal of epidemiology, 1990)
Familial occurrence of three definitive and two possible cases of Creutzfeldt-Jakob disease (CJD) with temporal and spatial separation in the area of focal CJD accumulation in Slovakia is reported. Incubation period is 51 and 53 years respectively, if spatial and temporal separation of affected siblings is considered, and 51 years when the time interval between the death of the affected mother and the clinical onset in the first affected child is determined. Affected children tend to die at the same time (mean difference 3.3 years) and not at the same age (mean difference 6 years). Due to separation of the affected children, a possible common exposure to CJD infection was limited to approximately seven years during their childhood. Potential endo- and exogenous risk factors and a possible mode of CJD transmission in the described family, as well as in the CJD focus, is discussed.
Keywords: Animals; Female; rodina; Creutzfeldt-Jakob Syndrome; ženské pohlaví; Československo; lidé; Male; Aged; Creutzfeldtova-Jakobova nemoc; Family; mozková kůra; Cerebral Cortex; lidé středního věku; senioři; zvířata; mužské pohlaví; Czechoslovakia; Middle Aged; Humans